Music and its effect on typing speed for clerical worker during postprandial somnolence state / Lin Yu Tong - Lin , Yu Tong (2016)
This research aims to examine the hypothetical assumption that music and its stimulative effect may increase typing speed for postprandial clerical workers. Past studies in postprandial somnolence generally focused on factors such as effects of food intake or biological clock on postprandial somnolence. However, there is a lack of research on the effect of music on typing speed for postprandial clerical workers. This study employed 50 clerical workers in two groups of twenty-five. They were exposed to three different environments; no music, slow music and fast music. The results and their answers in the questionnaire were recorded. 28 participants out of the 50 were then selected for further research as they displayed significant expression of postprandial sleepiness. The study also covered the possible disparity of effects on music exposure with or without headphones. Group 1 was exposed to music with the use of headphones whereas Group 2 was exposed to music without the use of headphones. Typing efficiency in the span of 120 seconds and questionnaire data were gathered and analysed with the use of SPANOVA, repeated measured ANOVA and Likert scale. The resulting outcome showed substantial influence of music, regardless of fast or slow paced, on the typing efficiency of the participants. Fast music induced more accuracy in the participants, however it is also of note that the participants who were exposed to fast music with the use of headphones scored better than the participants who were exposed to the same music without the use of headphones. An interesting observation remains, that participants who were exposed to slow music however, were able to type more words. This study proves that music helps to stimulate better performance and efficiency for postprandial clerical workers.